RPSE & reenactment of data using polynomial-variant cryptographic scheme in sensor environment. (2018) - Ambika, N.
Sensor environment relieves the hassle by monitoring the environment under study and providing results to the investigator in time. The users have to only endeavour about the whereabouts of the installations of these tiny elements in the environment under study. Such networks without any management and control can be intruded by the adversary. As a precautionary measure, encryption can be adopted. These encrypted messages are self-insured from being exposed unless the intruders have acquired the decryption keys. In this study, polynomial-variant is generated and used to encrypt the transmitted data. The variant is calculated using various properties of the nodes deployed. Adopting this protocol helps the base station to originate the manipulated data. The study preserves backward and forward secrecy. The work minimises wormhole attack and sinkhole attack in the network.